2017
DOI: 10.1021/acs.jpcc.7b00056
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance, Memory, and Reconfigurable Logic Functions Based on Monolayer Devices Derived from Gold Nanoparticles Functionalized with Electropolymerizable TEDOT Units

Abstract: We report on hybrid memristive devices made of a network of gold nanoparticles (10 nm diameter) functionalized by tailored 3,4-(ethylenedioxy)thiophene (TEDOT) molecules, deposited between two planar electrodes with nanometer and micrometer gaps (100 nm to 10 μm apart), and electro-polymerized in situ to form a monolayer film of conjugated polymer with embedded gold nanoparticles (AuNPs). Electrical properties of these films exhibit two interesting naphthalenethiol 8 or with 1-dodecanethiol 9 , a perylene deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 32 publications
(91 reference statements)
1
37
0
Order By: Relevance
“…A possible model that explains the nonlinear current–voltage characteristics at larger biases for networks containing a higher percentage of molecules can be based on tunneling transport and charge trapping . A modified Simmon's model provides a description of the relationship between tunneling current and the magnitude of applied bias in molecular systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible model that explains the nonlinear current–voltage characteristics at larger biases for networks containing a higher percentage of molecules can be based on tunneling transport and charge trapping . A modified Simmon's model provides a description of the relationship between tunneling current and the magnitude of applied bias in molecular systems.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, negative differential resistance (NDR) and hysteresis have aroused significant interest in the field of molecular electronics for applications including oscillators and amplifiers, analog‐to‐digital conversion, switching, memory, and neuromorphic circuitry . NDR and/or hysteresis have been observed using metallic contacts to a molecular monolayer containing nitroamine redox centers, molecular nanowires, and arrays of nanoparticles . Programmability in certain of these array systems can be achieved via applied gate voltage, modifying nanoparticle functionalization, or exposure to light .…”
Section: Introductionmentioning
confidence: 99%
“…Later, through further research, by redesigning the polymer structure, nonvolatile behavior can be induced. [61] Charge trapping is an inherent metastable mechanism, and the first neuromorphic device based on charge trapping showed retention of more than 10 3 s. [62] By adding a single layer of functionalized crystalline nanoparticles, the retention time can be extended to 10 5 s. [63]…”
Section: Stp and Ltpmentioning
confidence: 99%
“…Networks of metal nanoparticles linked by molecules (or for short NPSAN: nanoparticles self-assembled network) are very valuable and useful in molecular electronics to study fundamental electron transport mechanisms, as well as to assess their potential applications in nanoelectronics. [1][2] For instance, NPSANs with simple molecules (alkyl chains, short π-conjugated oligomers) have been used to gain new insights in metal-insulator transitions, [3][4] plasmon enhanced photoconductance, [5][6][7] and co-tunneling, [8][9][10][11] while NPSANs with relative complex molecules give access to functional devices such as optically [12][13][14][15] and redox 16 driven molecular switches, molecular memory and negative differential resistance, [17][18] and unconventional computing approaches. Bose et al demonstrated the training of molecule/ nanoparticle networks via genetic algorithms in an alkylthiol capped Au NPs network dominated by Coulomb blockade below 5K.…”
mentioning
confidence: 99%